SSCP Systems Security Certified Practitioner study guide - Murphy, George B. (Sybex, 2015)
Fully updated Study Guide for the SSCP This guide prepares you for the SSCP, Systems Security Certified Practitioner certification examination by focusing on the Common Body of Knowledge (CBK) as determined by ISC2 in seven high level topics. This Sybex Study Guide covers 100% of all exam objectives. You'll prepare for the exam smarter and faster with Sybex thanks to expert content, real-world practice, access to the Sybex online interactive learning environment and much more. Reinforce what you've learned with key topic exam essentials and chapter review questions. Along with the book you a.
Includes index. - Vendor-supplied metadata
Keywords: Computer networks -- Study guides -- Security measures -- Examinations; Telecommunications engineers -- Certification; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; COMPUTERS; Internet; Security; COMPUTERS; Networking; Security; COMPUTERS; Security; General; Computer networks; Security measures; Examinations; Telecommunications engineers; Certification; examination study guides; Study guides; Guides de l'étudiant